Processed animal manure improves morpho-physiological and biochemical characteristics of Brassica napus L. under nickel and salinity stress - Naveed, Muhammad; Ditta, Allah; Ahmad, Maryum; Mustafa, Adnan; Ahmad, Zulfiqar; Conde-Cid, Manuel; Tahir, Shermeen; Shah, Syed Atizaz Ali; Abrar, Muhammad Mohsin; Fahad, Shah (Environmental science and pollution research international, 2021)
Soil contamination with readily soluble salts and heavy metals is a major challenge concerning sustainable crop production. The use of organic wastes in agriculture not only helps in waste reduction but also acts as a soil conditioner and bio-stimulant for enhancing crop growth. In this regard, a pot experiment was conducted to investigate the effect of raw and processed animal manure (AM) on the growth, yield, and physicochemical parameters of Brassica napus L. developed under salinity and Ni stress. The experiment comprised two salinity levels (1.05 and 8 dS m-1), two Ni levels (0 and 50 mg kg-1), and two types of AMs (raw and processed at a rate of 2% w/w). A control treatment without AM incorporation was also included. In results, the application of AM markedly increased the growth and yield of B. napus under Ni and salinity stress; at the same time, it improved the physiological and chemical parameters of the said crop. Similarly, incorporation of processed AM significantly improved nutrient uptake and decreased Na/K ratios in the shoot and grain under the different stress conditions, as compared to the control. Likewise, Ni uptake in the grain, shoot, and root samples was also significantly reduced under the AM treatment. Also, the application of AM significantly reduced the daily intake of metal (DIM) index and the health risk index (HRI) values under the different stress conditions, as compared to the control. In conclusion, the application of processed AM constitutes an effective agricultural strategy to alleviate the adverse effects of Ni and salinity stress on growth, physiology, and yield of B. napus, thus resulting in enhanced productivity, as well as reduced risks associated with human health.
Keywords: Metals, Heavy; salinita; Humans; Health risk assessment; Soil Pollutants; látky znečišťující půdu; půda; lidé; Salinity; zvířata; hnůj; Manure; Animal manure; solný stres; nikl; těžké kovy; Salt Stress; Nickel; Brassica napus; Salinity stress; Brassica; Animals; Soil; Ni stress; Heavy metal